EMPOWERMENT OF INDIGENOUS COMMUNITIES IN PRESERVING LOCAL CULTURE AMID MODERNIZATION - Gunawan, Ratu Al Viola; Setiawati, Erlina (Bina Bangsa International Journal of Business and Management, 2025)
Empowering indigenous communities is the key to preserving local culture amidst modernization. This empowerment involves increasing the community's capacity to actively participate in preserving customs in the era of modernization. Modernization is a change in society's mindset and culture from a traditional one to a society with a modern mindset. In this increasingly advanced era, various challenges arise that can eliminate local cultural identity and local community knowledge about traditional traditions that have existed for generations. The method used in compiling this journal is a literature approach, namely by analyzing 50 national and international journals available on Google Scholar.   The aim of this research is to help indigenous peoples adapt in the era of modernization without eliminating their customs and cultural values ​​that have existed for a long time. From the results of this research, it can be illustrated that modernization has had a positive impact on easy access for people to learn about various customs and cultures in Indonesia. However, it will have a negative impact if people do not maintain their cultural identity.